2016
DOI: 10.1164/rccm.201510-2031oc
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Immune Cell Densities Are Associated with Lung Adenocarcinoma Gene Alterations

Abstract: Intratumoral immune cell densities (mDCs, CD8 T cells, neutrophils, macrophages) were significantly associated with molecular alterations in adenocarcinoma underlying the interactions between cancer cells and their microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 42 publications
2
54
0
Order By: Relevance
“…Recent research revealed that genetic mutations affected the response to immunotherapy by modifying TME . Lung adenocarcinomas with STK11 mutations had relatively lower levels of infiltrating CD4+/CD8+ T‐cells and PD‐L1 expression indicating a muted immune response .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research revealed that genetic mutations affected the response to immunotherapy by modifying TME . Lung adenocarcinomas with STK11 mutations had relatively lower levels of infiltrating CD4+/CD8+ T‐cells and PD‐L1 expression indicating a muted immune response .…”
Section: Discussionmentioning
confidence: 99%
“…mutations affected the response to immunotherapy by modifying the immune tumor environment (TME). [18][19][20] In this study, we compared the efficacy of immunotherapy in Asian versus white patients with NSCLC who participated in the blood samplebased OAK and POPLAR trials of atezolizumab versus docetaxel for patients with previously treated NSCLC. The clinical, pathological and genetic features of the two ethnic groups were analyzed to explore the possible mechanisms underlying the different outcomes.…”
Section: What's New?mentioning
confidence: 99%
See 1 more Smart Citation
“…), which could influence PD-L1 expression and the composition of the tumor microenvironment. 45,46 However, our other control group of EGFR-mutated lung tumors was well defined and homogeneous and ALK-positive lung cancer patients clearly displayed a higher frequency of predictive biomarkers of clinical response than this control group.…”
Section: Cd8mentioning
confidence: 64%
“…However, it is of note that a recent study that analyzed the correlation between intra-tumoral immune cell densities and genetic alterations in lung adenocarcinomas found that intra-tumoral macrophage density was significantly lower in tumors with EGFR mutations compared with those with wild-type EGFR (23). In this study, the density of neutrophils was also lower in lung cancers with EGFR mutations, while the densities of CD8 positive T-cells (cytotoxic T cells) and mature dendritic cells were identical.…”
Section: Anti-pd-1 / Pd-l1 Immunotherapy No Immunotherapymentioning
confidence: 99%